Suburban crime: the interplay of social, cultural and opportunity structures - Marwah, Sanjay (Criminal justice recent scholarship, 2006)
Structural analysis and crime research -- History and relevance of opportunity structures -- Suburban stratification and crime in the metropolis -- An examination of suburban Los Angeles -- Resource distribution & crime and violence